Musical Creativity in Autism: Exploring Growth through Collaborative Peer Interaction. Issue 1 (2nd January 2022) - Johnson, Erik; LaGasse, A. Blythe
ABSTRACT: Persons with Autism Spectrum Disorder (ASD) may have strengths in musical skills and music perception. Some children with ASD may also have better social engagement in music activities, making music a potential strength for interacting with others. Although children with ASD may be mainstreamed into music education classes, there is little known research on the impact of peer support. The purpose of this project was to examine the impact of peer-assisted learning (PAL) on musical creatiFvity and pro-social skills, between neurotypical (NT) and students with ASD. The following questions were investigated: (a) does music making with a peer impact music creativity differently in NT children and children with ASD, (b) does music making with a peer promote pro-social skills differently in NT children and in children with ASD. The sample included eighteen children with ASD and twenty-eight children with no known disability, between the ages of 9–14. Results of this study provide initial evidence that PAL experiences may be mutually beneficial for children with ASD and NT peers. In particular, an increase in pro-social skills were observed for some children grouped with NT peers, while the amount of time in creative music-making was similar between NT and NT/ASD peer groups.